2001
DOI: 10.1053/jhep.2001.25758
|View full text |Cite
|
Sign up to set email alerts
|

Increased Extracellular Matrix Remodeling Is Associated With Tumor Progression in Human Hepatocellular Carcinomas

Abstract: Matrix metalloproteinase-2 (MMP2) is a key enzyme in the process of extracellular matrix remodeling involved in tumor invasion and metastasis. The activation of MMP2 involves interplay with the membrane type-matrix metalloproteinase-1 (MT1-MMP) and the tissue inhibitor of metalloproteinase-2 (TIMP2). In vitro, activated hepatic stellate cells are a main source of MMP2 and collagen I induces MMP2 activation. The steady-state mRNA levels of MMP2, MT1-MMP, TIMP2, collagen I, collagen IV, and laminin ␥1 were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
129
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(138 citation statements)
references
References 44 publications
9
129
0
Order By: Relevance
“…Changes in the ECM composition of the liver, including increased deposition of collagen IV a1 and a2 in the space of Disse, are also characteristic of other pathological conditions of the liver such as cirrhosis (Neubauer et al, 2001;Yang et al, 2003;Zeisberg et al, 2006) and are the hallmark of the tissue-repair response of this organ. Tumor cell entry into the liver may trigger this repair process through localized tissue injury and these changes to the tumor microenvironment may, in turn, provide additional scaffolding for tumor cell adhesion and migration (Malinda and Kleinman, 1996;Habeck, 2001) and cues for cell proliferation in the otherwise tightly controlled, nonpermissive microenvironment of the liver (Bissell, 2001;Theret et al, 2001).…”
Section: Lung Metastasismentioning
confidence: 99%
“…Changes in the ECM composition of the liver, including increased deposition of collagen IV a1 and a2 in the space of Disse, are also characteristic of other pathological conditions of the liver such as cirrhosis (Neubauer et al, 2001;Yang et al, 2003;Zeisberg et al, 2006) and are the hallmark of the tissue-repair response of this organ. Tumor cell entry into the liver may trigger this repair process through localized tissue injury and these changes to the tumor microenvironment may, in turn, provide additional scaffolding for tumor cell adhesion and migration (Malinda and Kleinman, 1996;Habeck, 2001) and cues for cell proliferation in the otherwise tightly controlled, nonpermissive microenvironment of the liver (Bissell, 2001;Theret et al, 2001).…”
Section: Lung Metastasismentioning
confidence: 99%
“…Upon the occurrence of liver injury, activated hepatic stellate cells (HSC) contribute to the inflammatory response by secretion of MMPs resulting in ECM remodelling and increased matrix deposition [135]. ADAMs are also implicated in hepatocellular carcinoma development [136].…”
Section: Liver Carcinomamentioning
confidence: 99%
“…It has been reported that MMP2 activity on the cell surface might facilitate HCC invasion and progression. 40,41 All these results together demonstrate that GA effectively inhibits HCC invasion in vitro and metastasis in vivo.…”
Section: Tumor Immunologymentioning
confidence: 71%